Functional specificity of liquid-liquid phase separation at the synapse - Natalie J. Guzikowski; Ege T. Kavalali (Nature Communications)
Abstract The mechanisms that enable synapses to achieve temporally and spatially precise signaling at nano-scale while being fluid with the cytosol are poorly understood. Liquid-liquid phase separation (LLPS) is emerging as a key principle governing subcellular organization; however, the impact of synaptic LLPS on neurotransmission is unclear. Here, using rat primary hippocampal cultures, we show that robust disruption of neuronal LLPS with aliphatic alcohols severely dysregulates action potential-dependent neurotransmission, while spontaneous neurotransmission persists. Synaptic LLPS maintains synaptic vesicle pool clustering and recycling as well as the precise organization of active zone RIM1/2 and Munc13 nanoclusters, thus supporting fast evoked Ca2+-dependent release. These results indicate although LLPS is necessary within the nanodomain of the synapse, the disruption of this nano-organization largely spares spontaneous neurotransmission. Therefore, properties of in vitro micron sized liquid condensates translate to the nano-structure of the synapse in a functionally specific manner regulating action potential-evoked release.